Insight on passivity of high entropy alloys: Thermal stability and ion transport mechanisms in the passive oxide film on CoCrFeMnNi surfaces. (1st August 2021) - Wang, Luntao; Seyeux, Antoine; Perriere, Loïc; Mercier, Dimitri; Maurice, Vincent; Marcus, Philippe
Highlights: Passivity of CoCrFeMnNi high entropy alloy surfaces investigated by ToF-SIMS. Bilayer structure formed in aqueous acid solution thermally stable in vacuum. Further oxidation in low pressure O2 gas studied in situ with isotopic 18 O tracing. Outward cation diffusion faster than inward oxygen diffusion at 170 °C. Parabolic law of re-oxidation established and parabolic constant determined. Abstract: The ion transport mechanisms in passive films pre-formed on CoCrFeMnNi high entropy alloy surfaces in acid solution were studied in-situ by time-of-flight secondary ion mass spectrometry upon oxidation in 18 O2 gas. The bilayer structure of the passive film, with outer Fe, Co-rich and inner Cr, Mn-rich layers, is thermally stable, but with reduction of Fe and Co oxides and formation of Mn oxide in the outer layer above 150 °C. At 170 °C, the transport mechanism is mainly outward cation diffusion with slower inward oxygen diffusion. The re-oxidation growth rate follows a parabolic law and the value of parabolic constant was determined.